Analysis of the Effect of QUIC and TCP on Quality of Experience (QoE) during Handover - Muhammad Adlan Hafizha; Aji Gautama Putrada; Ryan Lingga Wicaksono (School of Computing, Telkom University, 2026)
Video streaming on mobile devices experiences interruptions when the wireless connection switches to a new network. This study aims to evaluate Quick UDP Internet Connections (QUIC) protocol’s performance as an alternative to Transmission Control Protocol (TCP) that oftentimes encounters performance setbacks during handovers. The simulation was performed using Mininet-WiFi emulator with a topology of two Access Points with various bandwidth capacities (10 Mbps to 1000 Mbps) and one mobile station (client). The simulations were repeated 30 times to ensure statistical validity for packet loss, latency, throughput, and buffering time metrics. Simulation results show that QUIC outperforms TCP in network metrics performance. QUIC’s Connection ID and 0-RTT initiation features reduce packet loss by up to 6.39%, maintain latency below 0.14 ms, and instantly restore throughput. However, an anomaly was found at high bandwidth (>500 Mbps) where buffering time of QUIC was longer due to the computational load of TLS 1.3 decryption in user space. Although QUIC is strong in wireless mobility, the CPU processing of the receiver’s device must be optimized on high-speed network.